Revealing Potency of Bioactive Compounds as Inhibitor of Dengue Virus (DENV) NS2B/NS3 Protease from Sweet Potato (Ipomoea batatas L.) Leaves - Viol Dhea Kharisma1,2, Rasyadan Taufiq Probojati1 , Ahmad Affan Ali Murtadlo1 , Arif Nur Muhammad An (Institute of Medico-legal Publications Pvt Ltd, 2021)
his study aims to identify the potency of bioactive compounds of sweet potato leaf as inhibitory agentto dengue virus (DENV) NS2B/NS3 protease by using computational study. The 3D structure of NS2B/NS3 protease was collected from PDB and the 2D structure of several bioactive compounds of sweetpotato leaf were obtained from PubChem. The visualization and data analysis were performed by usingthe PyMol software. According to the in silico analysis, result demonstrated that dehydroabietinol had thelowest free energy binding. However, based on the protein-ligand analysis, all the compounds showed thehydrogen bond and hydrophobic interaction. All the compounds with hydrogen bond could not be interactedwith catalytic domain, but hydrophobic interaction could be interacted to the target domain via Ser135 by?-Selinene and His51 by ?-Caryophyllene. In summary, we conclude that ?-Selinene and ?-Caryophyllenemight have potencies as a therapeutically drug for dengue.